Nuclear Reactor Thermal Hydraulics - Masterson, Robert E., 1970- (Boca Raton : CRC Press LLC, 2019)
Nuclear Thermal-Hydraulic Systems provides a comprehensive approach to nuclear reactor thermal-hydraulics, reflecting the latest technologies, reactor designs, and safety considerations. The text makes extensive use of color images, internet links, computer graphics, and other innovative techniques to explore nuclear power plant design and operation. Key fluid mechanics, heat transfer, and nuclear engineering concepts are carefully explained, and supported with worked examples, tables, and graphics. Intended for use in one or two semester courses, the text is suitable for both undergraduate and graduate students. A complete Solutions Manual is available for professors adopting the text.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Energy; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Engineering / Mechanical; Nuclear reactors -- Cooling; Nuclear reactors -- Fluid dynamics; Nuclear reactors -- Safety measures; Thermal hydraulics